PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA EMITEN ILQ 45 - Anggrayni, Selvia Ahyu; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe Purpose of this research is to empirically net profit margin, return on assets, return on equity, and earning per share to the stock price on LQ 45 index companies which are listed in 2013-2015. This research has been done by using multiple regression analysis and the are 28 companies and the total 84 observations LQ 45 index companies in Indonesia Stock Exchange in 2013-2015 periods. The secondary data has been obtained from Indonesia Stock Exchange. The analysis instrument has been done by using the SPSS version 21.0. The result has been obtained based on the goodness of fit test showed that the regression models is feasible to be used to predict net profit margin, return on asset, return on equity and earnings per share to the stock price to the LQ45 index companies in Indonesia Stock Exchange. The result of determination coefficient (R2) is 26,4% this figure has substantial contribution where as 73,6% is caused by other variables. The result of hypothesis test shows that partially the significant value of t test < 0,05 then the independent variables, i.e. NPM is 0.022; ROA is 0.041; ROE is 0.009; and EPS is 0,023 give positive and significant influence to the share price (closing price).Keywords : net profit margin, return on assets, return on equity, earning per share, stock price